Personality characteristics of students in the regulation of network activity - S. E. Panshina; N. L. Sungurova; N. B. Karabushchenko (Russian State Vocational Pedagogical University, 2021)
Introduction. Nowadays, the increasing Internet influence on the personality and the ambiguous nature of this impact frequently result in such negative consequences as Internet addiction, reduced self-control, and dysregulation of the Internet-activity. Therefore, it is becoming more and more relevant to investigate the characteristics of personality regulation of students' network activity. The aim of the current research was to identify personality characteristics, which determine the network activity of students. Methodology and research methods. The current research is based on a subject-personal approach. The following methods were applied: Internet Behaviour Questionnaire (by A. E. Zhichkina); Self-Organisation Activities Questionnaire by E. Yu. Mandrikova (OSD); modified questionnaire (by O. N. Arezdova, L. N. Babanin, A. E. Voiskunsky); questionnaire "Attitudes towards the Internet" (by E. Gubenko); Cognitive Emotion Regulation Questionnaire in the adaptation of O. L. Pisareva and A. Gritsenko; the technique of M. Kernis and A. Paradise "The Contingent Self-Esteem Scale" adapted by T. N. Savchenko, A. G. Faustova; personality questionnaire (TIPI-RU) (by A. S. Sergeeva, B. A. Kirillov, A. F. Dzhumagulova). Results and scientific novelty. For the first time, personality regulation of network activity is considered as a system of personality formation, which includes the following components in its structure: regulatory-behavioural, need-motivational, cognitive-emotional, and reflective-evaluative. General trends in the identified components and the connection of network behaviour strategies with personality characteristics of the student audience are determined. Students are characterised by an understanding of their own goals and their desire to achieve them, a tendency to be consistent and to follow the scheduled structure of the organisation of events, the manifestation of will to achieve goals and developed tactical planning skills. The Internet for students is above all a comfortable environment, where it is possible to feel calm and security, to expand social contacts, to find a new experience. Students are more likely to use effective strategies for cognitive emotion regulation, which are aimed at searching for the ways to overcome adverse situations, at recognising the positive significance of the event for personal growth, as well as at accepting the situation. Respondents' self-esteem is moderately reactive to the impact of situational factors. Students, who prefer network behaviour strategy "Activity in action", have a generally positive personality profile, they tend to choose favourable strategies of cognitive emotion regulation, and they have personality characteristics such as determination, perseverance, extroversion, openness to new experience. The personal characteristics of young people with the strategy "Activity in the perception of alternatives" and "Internet addiction" are represented by the choice of negative cognitive emotion regulation strategies, situational conditioning of self-attitude, and attitudes toward problematic Internet use. Practical significance. The research results can be used to improve distance learning programmes, additional education courses, as well as to increase the efficacy of regulation of student's network activity in order to prevent Internet addiction.